Getting wet: Tales of lesbian seductions - Allain, Carol; Elwin, Rosamund (Women's Press, 1992)
This is sex fiction that gets under the covers and rolls them back, sex fiction that inscribes lesbian erotics poignantly, playfully and powerfully.
Keywords: 1900-1999; amériques; approches et analyses; canada; corps; lesbianisme; périodes historiques; ressource en ligne; régions géographiques; sexualité; thématiques; érotisme